Design and implementation of AMBA bridge protocol in system on chip design - Wang Hang Suan; Asral Bahari Jambek; Mohd Nazrin Bin Md Isa; Azizi bin Harun; Shaiful Nizam Bin Mohyar; Zulfiqar Ali Bin Abd. Aziz (Institute of Advanced Engineering and Science, 2019)
The Advanced Microcontroller Bus Architecture (AMBA) is widely used in modern technology device. The design of bridge in the system is due to increase demand of power consumption and functionality. The bridge help to reduce power by separate the system into high bandwidth and low bandwidth. The goal of this paper is to design and implement the AMBA bridge into a SoC design which consists of a processor, RAM, ROM, watchdog and LED module. These peripherals are connected separately based on different bandwidth with a bridge as the medium. The result shown the bridge transfer a correct data from the ROM into the RAM. The experiment was carry out using Synopsys 2017 and Keil uVision.